2022
DOI: 10.1021/acsomega.2c03927
|View full text |Cite
|
Sign up to set email alerts
|

Chlorfortunones A and B, Two Sesquiterpenoid Dimers, Possessing Dispiro[4,2,5,2]pentadecane-6,10,14-tren Moiety from Chloranthus fortunei

Abstract: Chlorfortunones A ( 1 ) and B ( 2 ), two novel sesquiterpenoid dimers, were isolated from the roots of Chloranthus fortunei . Their structures were elucidated by spectroscopic analysis and X-ray diffraction analysis. Compounds 1 and 2 represent a new type of sesquiterpenoid dimer possessing an unprecedented 3/5/6/6/6/5 hexacyclic system with a unique dispiro[4,2,5,2]pentadecane-6,10,14-trien moiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…72 Besides the abundant LSs with conjugated units, non-LSs with different skeletons can serve as diene or dienophile units to form hetero-[4 + 2] LS oligomers. 36,37,65,71 The second category of LS oligomers occurs through [2 + 2] cycloaddition between two D 8 ′ (9 ′ ) and [6 + 6] cycloaddition between the highly conjugated D 15(4),5(6),7 (11) , which is uncommon in nature. 70,[73][74][75][76] There will still be highly conjugated fragments in the oligomers of LSs aer the occurrence of [6 + 6] cycloaddition, also suggesting that the subsequent intramolecular rearrangement and cyclization products will be very rich and unusual (Fig.…”
Section: Structural Classicationmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Besides the abundant LSs with conjugated units, non-LSs with different skeletons can serve as diene or dienophile units to form hetero-[4 + 2] LS oligomers. 36,37,65,71 The second category of LS oligomers occurs through [2 + 2] cycloaddition between two D 8 ′ (9 ′ ) and [6 + 6] cycloaddition between the highly conjugated D 15(4),5(6),7 (11) , which is uncommon in nature. 70,[73][74][75][76] There will still be highly conjugated fragments in the oligomers of LSs aer the occurrence of [6 + 6] cycloaddition, also suggesting that the subsequent intramolecular rearrangement and cyclization products will be very rich and unusual (Fig.…”
Section: Structural Classicationmentioning
confidence: 99%
“…28 Subsequent oxidative rearrangement further enhances the structural diversity, such as sarglaromatic D, 68 fortunoid A, 69 and chlorahupetone G. 70 Meanwhile, Δ 15(4),5(6) can also react with Δ 11′(13′) and Δ 15′(4′) or other double bonds of the non-LS unit. 71 Also, Δ 7(11),8(O) can exist as a diene moiety and undergo oxygenate [4 + 2] cycloaddition. 72 Besides the abundant LSs with conjugated units, non-LSs with different skeletons can serve as diene or dienophile units to form hetero-[4 + 2] LS oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the more polar methanolic fraction was subjected to chromatographic separation, which resulted in the isolation and identification of one new diterpenoid with a novel prenylmaaliane-type skeleton (1), three new prenylaromadendrane-type diterpenoids (2)(3)(4), four new cembrane-type diterpenoids (5)(6)(7)(8)(9), and three known compounds (10)(11)(12). As one part of our ongoing screening of lead compounds for inhibiting TGF-β from natural products [24][25][26], the TGF-β inhibitory activities of isolated compounds were evaluated in LX-2 human hepatic stellate cells, and the results showed that compounds 1 and 5 exhibited TGF-β-inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the sesquiterpenoid dimer chlorfortunone A 19 , from Chloranthus fortunei , was established by X-ray analysis. 17 Chlorfortunone A 19 possesses a novel dispiro hexacyclic ring system that the authors suggest is formed by a Diels–Alder cycloaddition between lindenane and acorane sesquiterpenoid precursors. The structure of the chamigrane sesquiterpenoid dimer antroxazole A 20 , from Antrodiella albocinnamomea , was also established by X-ray analysis.…”
mentioning
confidence: 99%